Correlation of regional cerebral blood flow equivalents measured by single photon emission computerized tomography with P300 latency and eye movement abnormality in schizophrenia. - Blackwood, D; Ebmeier, K; Muir, W; Sharp, C; Glabus, M; Walker, M; Souza, V; Dunan, JR; Goodwin, G (1994)
Single photon emission tomography with the intravenous blood flow marker 99mTc-exametazime was carried out in 14 acutely ill drug-free schizophrenic patients from whom P300 event-related potential, smooth eye pursuit eye tracking and verbal fluency were measured within a few days of scanning. Smooth pursuit eye movement abnormality correlated significantly with abnormal tracer uptake in superior pre-frontal cortex on the right and left and inferior pre-frontal cortex on the left. Abnormal eye movement was also associated with higher tracer uptake in left anterior cingulate and left posterior cingulate. P300 latency was significantly correlated with higher tracer uptake in left superior pre-frontal and left parietal regions. Verbal fluency performance was negatively correlated with tracer uptake in left frontal region. Eye tracking abnormality in schizophrenia is associated with bilateral frontal lobe disturbance and P300 latency increase with left-sided frontal and temporoparietal dysfunction. There was, however, a significant inverse relation between eye tracking abnormalities and abnormal perfusion in the left anterior cingulate region.